Online Shopping Behavior: The Influence of Online Reviews on Consumer Purchasing Decisions - Daisy Mui Hung Kee; Subashini A/P Lourdusamy; Siti Wardah binti Noor Azman; Siti Nursriaini binti Abdullah; Siti Zakiyah binti Rofie (Journal of The Community Development in Asia, 2026)
This study explores how online reviews influence consumer purchasing decisions on popular e-commerce platforms such as Google, Shopee, Lazada, and TikTok Shop. The main purpose of the research is to understand how factors like review credibility, quantity, and tone affect customers trust and willingness to buy products online. A quantitative approach was used, where 200 online shoppers in Malaysia were surveyed through a structured questionnaire. The collected data were analyzed using descriptive and regression analysis to determine the strength of the relationship between online reviews and consumer decisions. Our findings indicate that trustworthy and positive reviews strongly encourage consumers to make purchases, while negative or unclear reviews cause them to hesitate or seek other options. The study concludes that online reviews are an important factor in shaping consumer confidence and purchase behavior. It is suggested that online sellers and platforms focus on encouraging honest reviews and responding to feedback to build stronger relationships and loyalty among customers.